2006
DOI: 10.1177/0003319706290741
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk of Rupture of Abdominal Aortic Aneurysms by Utilizing Various Geometrical Parameters: Revisiting the Diameter Criterion

Abstract: The authors estimated noninvasively the wall stress distribution for actual abdominal aortic aneurysms (AAAs) in vivo on a patient-to-patient basis and correlated the peak wall stress (PWS) with various geometrical parameters. They studied 39 patients (37 men, mean age 73.7 +/- 8.2 years) with an intact AAA (mean diameter 6.3 +/- 1.7 cm) undergoing preoperative evaluation with spiral computed tomography (CT). Real 3-dimensional AAA geometry was obtained from image processing. Wall stress was determined by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 39 publications
(40 reference statements)
3
72
0
2
Order By: Relevance
“…As a result the AAA, which commonly does not rupture in the supported region, usually ruptures in the posterolateral sites due to the retroperitoneal cavity [1]. On the other hand, higher surface curvature [53] and centerline asymmetry [54] have been associated with higher wall stress. Patient-specific aneurysm models were shown to rupture mostly at regions of high stress (inflection regions) [36,55] which were not necessarily the regions of lowest wall thickness.…”
Section: Discussionmentioning
confidence: 99%
“…As a result the AAA, which commonly does not rupture in the supported region, usually ruptures in the posterolateral sites due to the retroperitoneal cavity [1]. On the other hand, higher surface curvature [53] and centerline asymmetry [54] have been associated with higher wall stress. Patient-specific aneurysm models were shown to rupture mostly at regions of high stress (inflection regions) [36,55] which were not necessarily the regions of lowest wall thickness.…”
Section: Discussionmentioning
confidence: 99%
“…27 Circulating levels of several markers of extracellular matrix degeneration with biological plausibility have been correlated with AAA progression, such as elastin peptides, aminoterminal propeptide of type III procollagen, elastase-a1-antitrypsin complexes, matrix metalloproteinase 9, cystatin C, plasmin-antiplasmin complexes, and tissue plasminogen activator. 27 Others supported that a quantitative 3-dimensional tortuosity index of the AAA shape 28 or the peak wall stress and the mean centerline curvature of the AAA 29 may be better predictors of the AAA rupture potential than AAA size. Although promising results have been reported, no definite conclusions can be drawn yet.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced patient-specific computational models can be used to assess the correlation between PWS and 3D geometric features. Giannoglou et al (Giannoglou et al, 2006) reported a strong relationship between PWS values and the centerline curvature in AAA models, whereas Doyle et al (Doyle et al, 2010) advocated a correlation between PWS and centerline asymmetry. Both studies were based on computational models without taking into account the presence of thrombus.…”
Section: Evaluating the Aaa Geometrymentioning
confidence: 99%